(untitled) (Encuentros, 2017)
Paraguay is one of the few countries in South America that has two official languages. Guaraní is one of them and it is a staple of national identity. Nonetheless, the use of Guarani seems to be decreasing steadily. The government and Guarani speakers do not actively promote its use in society. This research seeks to identify the link between the tacit appreciation that Paraguayans confess towards Guaraní and—conversely—the negative connotations attributed to its use in society.